Joshyy32go Joshyy32go Math Answered Transform the following quadratic functions into the form () = ( − ℎ)2 + .A. by Completing the Square1. () = 2 + 6 + 14 () = (________) + 14 () = ( 2 + 6 + ___) + 14 − ____ () = ( + ____) 2 + _____2. () = 2 2 + 8– 1 () = ( _________ ) – 1 () = 2 ( 2 + ___ ) − 1 () = 2 ( 2 + 4 + ____ ) − 1 – 2(4) () = 2 ( + 2 ) 2 − 1 – 8 () = 2 (_________ ) 2 − ____3. () = 2 – 4 + 7 () = ( _______ ) + 7 () = ( 2 – 4 + ____ ) + 7 − ____ () = (_______ ) 2 + _____PASAGOT NAMAN NG MAAYOS, KUNG DI ALAM YUNG SAGOT WAG NA LANG SUMAGOT!THANKS!